Pengembangan Multimedia Interaktif Pembelajaran IPA-Biologi Menggunakan Macromedia Flash 8 untuk Peserta Didik Kelas VIII SMPN 34 Padang - Tiffany Mantoviana; Linda Advinda; Moralita Chatri; Dwi Hilda Putri (Postgraduate, University of Mataram, 2023)
The purpose of this research is to produce interactive multimedia using Macromedia Flash 8 for class VIII students at SMPN 34 Padang with material on the respiratory system and human excretory system that is valid, practical and effective. The data collection instruments used were interactive multimedia validation sheets by 3 validator lecturers, interactive multimedia practicality questionnaires by science teachers and students, as well as observation sheets on cognitive, affective, psychomotor aspects and learning activities. The results of the validation assessment by the validator of interactive multimedia on material on the human respiratory system and excretory system showed an average value of 82.33% (very valid). The results of the practicality assessment by science teachers showed an average score of 85.51% (very practical) and the results of the practicality assessment by students showed an average score of 91.64% (very practical). The results of the effectiveness test of interactive multimedia using Macromedia Flash 8 from the cognitive, affective, psychomotor and student activity aspects show that interactive multimedia using Macromedia Flash 8 is very effective. Thus, it can be concluded that the interactive multimedia using Macromedia Flash 8 developed is very valid, very practical and very effective.